Consumption of food groups and associated factors among children aged 6 to 23 months - Siqueira,Ilanna Mirela Becker Jorge (2022)
Abstract Objective: To assess the consumption of food groups among children aged 6 to 23 months in day care centers and at home and its associated factors. Methods: This is a population-based cross-sectional study conducted with children from nursery schools in Guaratuba, Paraná. Parents answered a socioeconomic and demographic questionnaire. Food consumption was assessed by directly weighing the meals offered at the day care center. At home, parents filled an estimated food record. The reported foods were classified into seven food groups. Minimum dietary diversity was calculated by the proportion of children who consumed foods from four or more groups. Data were analyzed by simple and multiple logistic regression, presented as odds ratios. Results: A total of 213 children participated in this study. The average number of food groups consumed was 4.2±1.0 at home and 4.2±1.2 in day care centers. At the day care center, all children consumed grains, roots, and tubers, while at home, this rate was 99.1%. The egg group was the least consumed both at day care (6.6%) and at home (2.8%). At home, more than 60% of children consumed sweets and sugar-sweetened beverages. Children aged 12 to 23 months were more likely to consume milk and dairy products, as well as flesh foods. Higher income was associated with the consumption of legumes, and older maternal age with the consumption of fruits and vegetables. Conclusions: At home, children had a predominantly dairy-based diet and a high intake of ultra-processed foods. In day care centers, the consumption of healthy foods was higher, indicating the need for families to participate in the formation of healthy eating habits.